(3GdEJLGQ HGdHTQ Hjf Gdabg GdESdGei h GdbGfhf GdhVYi (B/ s - (3YHO GdgGOj gGTe YHO GdgGOjs; (3WGQb CMeO aJMi SQhQs; (3eMeO fLjH YhVjfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3GdfGXQ aj YUQfG GdMGVQ jLO hHcd CSa Cf GdEfSGf GdPj cQeg Gddg SHMGfg hJYGdi JMhd Gdi SdYI JHGY hJSJZd BOejJg CShC GSJZdGd dPG GNJQJ gPG GdehVhY(B. (3hgPg GdLQjeI dgG Yeb JGQjNj, hMJi jJSfi dfG eYQaI gPg GdLQjeI dGHO dfG ef Gdhbha Ydi JWhQgG GdJGQjNj heGgjJgG hCQcGfgG hCge UhQgG hcjajI ecGaMJgG aj Gdabg GdESdGej hGdbGfhf GdhVYj hHjfJ ecGfI GdEfSGf heXGgQ JcQjeg hGdJWhQ GdJGQjNj dacQI GdGJLGQ HGdHTQ aj Gdabg GdESdGej hGdbGfhf GdhVYj hJMOKJ Yf eGgjI GdGJLGQ HGdHTQ hNUGFUgG hCQcGfgG hGdJejjR HjfgG hHjf eG jJTGHg eYgG(B. (3hehba Gdabg GdESdGej ef LQjeI GdGJLGQ HGdHTQ, Ke HjfJ cjajI ecGaMI gPg GdLQjeI aj Gdabg GdGSdGej hGdbGfhf GdhVYj hJhUdJ GdfJGFL Edi Mb GdGfSGf aj GdcQGeI GdEfSGfjI hCf LQjeI GdGJLGQ HGdHTQ XGgQI JGQjNjI bOjeI hJhUdJ GdfJGFL Edi MQeI GSJZdGd GdHTQ aj Gdabg hGdbGfhf(B.s
(3CWQhMI (B( (3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFj (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ (B381-399.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFj GdebGQfs; (3GdEJLGQ HGdHTQs; (3GdEJLGQ HGdCWaGd s; (3GdbGfhf GdLfGFi GdOhdis; (3LQjeI GdGJLGQ HGdHTQs; (3NWa GdCWaGds; (3GdGSJZdGd GdLfSjs; (3GdJShds; (3GSJZdGd GdCWaGd aj GdYeds; (3GdJTQjY GdLfGFi GdeUQis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs